Relationship between Competency, Motivation, Workload and Leadership with the Performance of Administrative Staff in GMIM Bethesda General Hospital - Sjeddie R. Watung (Journal of International Conference Proceedings (JICP), 2022)
All administrative staff of the GMIM Bethesda Tomohon General Hospital have their respective job descriptions that have been determined by the hospital management, but the implementation has not been carried out optimally. This is evidenced by the fact that there are still complaints of dissatisfaction from the community regarding the services provided. The purpose of this study was to analyze the relationship between competence, motivation, workload and leadership with the performance of administrative staff at the General Hospital GMIM Bethesda Tomohon. This research is an observational analytic study with a cross-sectional approach. The population is all administrative staff at the General Hospital GMIM Bethesda Tomohon with a total of 54 employees. The data were collected by using a questionnaire filled out by the employees themselves, and the data were analyzed univariately through a frequency distribution table, bivariate analysis with chi-square test and multivariate with logistic regression method. The results of the analysis show that there is a relationship between competence, motivation, workload dan leadership with staff performance dan there is a most dominant variable on the performance of administrative staff is leadership.Keywords: Competency, Leadership Motivation, Performance, Workload.